IMPLEMENTATION OF A BALANCED NUTRITION EDUCATION PROGRAM AMONG PRIMARY SCHOOL CHILDREN IN TURKEY - Besler, Halit Tanju; Meseri, Reci; Kucukerdonmez, Ozge; Sahin, Habibe; Cicek, Betul; Gunes, Esra; Mutus, Begum (Elsevier Science Inc, 2018)
[Abstract Not Available]
4th Nutrition and Healthy Lifestyles Summit of the Sabri-Ulker-Food-Research-Foundation on Effects of Eating Behavior on Health -- MAY 04, 2017 -- Istanbul, TURKEY